Investigation of the photoluminescence and absorption spectrum of GeSn nanoplatelets - Lim, Sherleen Ting Wei (Nanyang Technological University, 2023)
Germanium-tin (GeSn) alloys have recently gained attention due to their potential use in optoelectronic devices. In this project will apply the 10-band k.p method to simulate the band structure of GeSn under tensile strain and to obtain photoluminescence and absorption spectra on different strains and thicknesses. The k.p method is a widely used approach for calculating the band structure of GeSn QW. QWs consist of a thin layer of semiconductor material sandwiched between two layers of a different semiconductor material with a wider bandgap. The electrons and holes are confined within the thin layer, which creates discrete energy levels. However, the confinement is weaker, resulting in broader energy levels and lower absorption coefficients [1]. GeSn is a promising material for optoelectronic applications, and its band structure and optical properties can be tuned by applying strain. Our results show that the bandgap of GeSn decreases with thickness due to Quantum Confinement effect. The thickness of GeSn also affects its optical properties, with thinner samples showing a stronger PL and absorption. The PL and absorption spectrum showed a broader peak when the tensile strain increases. The study was conducted under 300K with ww varies from 100Å, 200Å, 300Å, 500Å, 700Å and 900Å with tensile strain of 0%, 0.2% 0.4% and 0.6% of [100] direction, are applied to study the PL and absorption spectrum on the TE and TM mode. This study provides valuable insights into the optical properties of GeSn nanoplatelets and can contribute to the development of future optoelectronic devices.